The role of work ethics in improving financial performance (Field study on the branches of the Commercial Bank of Syria No. (1) and (6) in Lattakia) (Journal of Hama University, 2021)
This study aimed to define the role of business ethics in improving the financial performance of commercial banks in Lattakia, by defining the role of business ethics dimensions (honesty and integrity, integrity and transparency, objectivity) in improving the financial performance of commercial banks.The researchers followed the descriptive and analytical method in their study, and a set of methods, including relying on secondary and primary data through a questionnaire that was designed and distributed to (99) individuals staff working in the Commercial Bank branches No. (1 and 6), from which they recovered (93), and it was (93). 89) Questionnaire suitable for analysis.Among the results presented by the study: Work ethics in its various dimensions (honesty and integrity, integrity, transparency, and objectivity) play an important role in improving financial performance, and this is what the results of hypothesis testing have shown, and the average responses of the sample members for the statements of the variable of honesty and integrity reached (4.167), and this It means the approval of the sample members to adopt honesty and integrity and take into account the balance of interests, and they have the professional ability to improve and perfect work and keep secrets, and to pursue honesty, integrity and bias in the interest of the bank.